Microfiber Filter Performance Prediction Using a Lattice Boltzmann Method (Communications in Computational Physics, 2020)
Fibrous filter media are made of small fibers (micro and nanoscale). In thesecases, the Knudsen number can be appreciable and the slip phenomenon on the fluidboundary surfaces should be considered. For this purpose, the mesoscopic approachlattice Boltzmann method (LBM) can be applied to predict the flow, with appropriateboundary conditions (BC). This paper analyzes a fibrous microfilter, including theconstruction of the geometric model from scanning electron microscope (SEM) images,and the comparison with experimental results and macroscopic approach modeling. Aslip condition was implemented in open-source code OpenLB, based on specular reflectionsof the populations. The validation of the proposed boundary condition wascarried out by simulations in a 2D channel, disposed at 45 and 90 degrees, and simplecases of a flow around an octagon. The experimental order of convergence (EOC) wasevaluated for all cases and the results of the pressure drop around the octagon werecompared to data obtained by a macroscopic approach. A good agreement between thepressure drop through the filter media and the results obtained numerically and experimentallywas observed. These findings endorse the accuracy of the implemented slipBC and the importance in considering this phenomenon in microscale systems.
Keywords: Filter medium; slip boundary condition; lattice Boltzmann method; microscale.